California Serogroup Virus Infection Associated with Encephalitis and Cognitive Decline, Canada, 2015 - Webster, Duncan; Dimitrova, Kristina; Holloway, Kimberly; Makowski, Kai; Safronetz, David; Drebot, Michael A. (Emerging infectious diseases, 2017)
California serogroup (CSG) viruses, such as Jamestown Canyon and snowshoe hare viruses, are mosquitoborne pathogens that cause febrile illness and neurologic disease. Human exposures have been described across Canada, but infections are likely underdiagnosed. We describe a case of neuroinvasive illness in a New Brunswick, Canada, patient infected with a CSG virus.